Analisis Risiko Keamanan di SDN Sipatahunan - Bahirah, Rafa' Ikram; Hidayat, Wahyu (PT. Cahya Edupreneur Indonesia, 2024)
This study aims to evaluate the policies, monitoring systems, and risk mitigation measures implemented by schools in maintaining student security while providing recommendations for improving school security management. The importance of maintaining student security in the school environment is a major supporter of the success of the education process. Effective security can create a comfortable and productive learning atmosphere. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews with the principal and homeroom teacher, as well as direct observation of security facilities and student activities. Related school documents, such as rules, incident reports, and security policies, were also systematically analyzed to support this study. The results of the study indicate that implementing various security policies, such as the formation of a Violence Prevention and Handling Team (TPPK), installing CCTV, and implementing strict rules, is quite effective. Although these steps are quite effective, there are several challenges, such as incidents of accidents and conflicts between students, which indicate the need to improve the monitoring system and training for the entire school community. This study shows a commitment to managing security risks, but these efforts still need to be strengthened through increased training, socialization of security policies, and development of emergency response procedures. With the right recommendations, it is expected to create a safer and more conducive learning environment for all students.